Carbon Nanotubes and Copper Oxide as Electro-Catalysts for Rechargeable Zinc-Air Batteries - Kornsai, Chonyada; Phuchahan, Sukunya; Ananpreechakorn, Watsayod (Indochina Applied Sciences, 2025)
CNTs and CuO will be used as electrocatalysts for redox reactions in rechargeable zinc-air batteries as the aim of this research. A carbon felt substrate was used to coat the CuO/CNTs composite, and the cathode properties were examined. Analyzed using XRD, FE-SEM, EDS, FT-IR, CV, and LSV. The results indicate that CuO/CNTs exhibits a monoclinic and hexagonal crystal structure, along with the presence of aromatic structures within the CNTs. The retention of PVDF was confirmed, and the composite demonstrated uniform dispersion on the carbon felt. The elemental composition was found to be C (54.52%), F (37.35% Cu (4.95%) and O (3.18%). At an applied voltage of 2 V, the current density increased from 0.66 to 6.92 mA cm–2, while at 2.40 V, the current density decreased from -0.34 to -3.67 mA cm–2. After 50 cycles, the current density declined by 5− 10%, indicating moderate electrochemical stability. The findings suggest that CuO/CNTs is a promising bifunctional electrocatalyst for both OER and ORR. Additionally, this research can be further developed into educational materials to enhance the understanding of zinc-air battery technology.